Strategy for Strengthening Arabica Coffee Agribusiness Institutions Through an Interpretative Structural Modelling Approach in South Sulawesi, Indonesia - Irmayani; Masnur; Darmawan Salman; Abdul Azis Ambar; Ammang Latifah; Rafi’ah Nur; Muhammad Amri Rahman (Jurnal AGRISEP, 2025)
Coffee exports are high, but productivity is low due to poor coordination, limited resources, and weak skills and infrastructure. The objectives of this research are to (1) explain the role of agribusiness institutions in enhancing the competitiveness of Arabica Coffee, (2) identify the obstacles that hinder the effectiveness of agribusiness institutions in enhancing Arabica Coffee production, (3) design strategic programs to improve Arabica coffee production. This research uses survey methods, interviews, and focus group discussions to obtain data by involving respondents or experts directly involved. The analysis used is Interpretative Structural Modeling to analyze institutional relationships and identify strategic points for policy intervention to increase Arabica coffee production.  The results of the ISM analysis show that the Department of Food Crops, Horticulture, and Plantations of Enrekang Regency has a strategic role in increasing Arabica coffee production through coordinated strategic programs. The main obstacle is the lack of initial support for institutional involvement, which hinders inter-agency coordination. Strategic programs such as extension services focus on enhancing farmers knowledge and skills to adopt sustainable technologies and practices.